MANAJEMEN LINGKUNGAN FISIK ( SERVICESCAPE ) DALAM RANGKA MENINGKATKAN KEPUASAN PELANGGAN PADA HOTEL SALAK THE HERITAGE - mawi, maswir (Politeknik Negeri Jakarta, 2018)
This study aims to know management servicescape to service quality seen from the service dimension (tangibility, reability, responsibility, assurance, empathy) so that it can affect customer satisfaction at the hotel salak the heritage. This study uses subject data. In this case the subject of his research is hotel salak the heritage. Methods of collecting data and information using three methods of observation, questionnaire, and literature study. Observation is by observing and participating directly in the implementation of work performed by employees, distributing questionnaires to several customers who are meeting and staying at Hotel Salak The Heritage to determine the level of customer expectations of services provided, and learn from the books in the library And find out which areas will be deepened and search the material through the internet and company website. The results showed that in managing the servicescape in the hotel should make management strategy in accordance with the operational plan and standard of the applicable procedures that must be obeyed by employees so that it can control the work system of employees. While customer satisfaction can be seen if the perceived performance is given greater than the customer expectations of service quality based on service dimensions (tangibility, reability, responsibility, assurance, empathy) that can have an important effect on the satisfaction or not the customer to the services provided that will have good impact Bad for the company'sÂ progress.